2019
DOI: 10.1108/apjie-07-2018-0045
|View full text |Cite
|
Sign up to set email alerts
|

Empowering small industry of wood carving handicraft in Bangli district

Abstract: Purpose The purpose of this study is to analyze the influence of social capital on human capital; the effect of social capital on transaction costs; the influence of social capital, human capital and transaction costs on empowerment; the indirect effect of social capital on empowerment through human capital; and the indirect effect of social capital on empowerment through transaction costs in Bangli Regency. Design/methodology/approach The population in this research is all wood carving business in Bangli Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The dynamic environment has a more organic organizational structure in small companies. According to Marhaeni et al (2019) human resources mediate part of the influence of social capital on empowerment; and transaction costs do not act as variables, mediating the effect of social capital on the empowerment of the small wooden handicraft industry in Bangli Regency. It is necessary for companies to adapt to the environment.…”
Section: H1mentioning
confidence: 99%
“…The dynamic environment has a more organic organizational structure in small companies. According to Marhaeni et al (2019) human resources mediate part of the influence of social capital on empowerment; and transaction costs do not act as variables, mediating the effect of social capital on the empowerment of the small wooden handicraft industry in Bangli Regency. It is necessary for companies to adapt to the environment.…”
Section: H1mentioning
confidence: 99%
“…Social capital positively influences entrepreneurial interest ( (Ali & Yousuf, 2019;Lee & Hallak, 2020;Mahfud et al, 2020;Marhaeni et al, 2019;Moghaddam et al, 2018b;Pruthi & Wright, 2019); (Lee & Hallak, 2020); Pruthi, 2019;Ali, 2019;Moghaddam, 2018;Marhaeni et al, 2019). (Finnah Fourqoniah, 2015)explains that social networking can be used as a medium to foster entrepreneurial interest in students based on the theory and connectivity of social learning.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…(Puspitaningsih, 2014) explains in her research that entrepreneurship knowledge among students is no significant effects on student's intention on entrepreneurship. While many researchers found that based on various previous research references, entrepreneurial interest is influenced by several variables, namely self-efficacy (J. E. Kurniawan, 2012), social capital (Marhaeni et al, 2019;Moghaddam et al, 2018a;Pruthi, 2014) entrepreneurial literacy (Orser et al, 2019;Park, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In the coastal area, many fishermen live in poor households. However, some researchers suggest that informal firms have a good social capital that can reduce transaction costs, making economic activity run efficiently, and innovation capability [48,49].…”
Section: Introductionmentioning
confidence: 99%